(untitled) (Dhaka University Journal of Biological Sciences, 2023)
The present experiment investigated whether different reading methods would have any effect on reading comprehension performance. It was hypothesized that reading comprehensive performance would be better with subvocalization than other reading methods. The independent variable was reading methods and the dependent variable was performance (speed and accuracy). To conduct this experiment, 60 school students were taken with age ranges from 8 to 10 years. The Latin Square design was used to conduct this experiment. Recall scores were obtained for each participant in terms of four reading methods: silent reading, subvocalization, reading aloud and listening music while reading. Results of the One-way ANOVA and Post Hoc test showed that only reading time vary among four reading methods. Multiple comparisons showed that there is a significant difference in reading time between silent reading and reading aloud. So, the result did not support the hypothesis of subvocalization as a better reading method. Dhaka Univ. J. Biol. Sci. 31(2): 225-230, 2022 (July)